Engine-compatible biodiesel from Leucaena leucocephala seed oil - Hakimi, M.I.; Khalilullah, -; Goembira, F.; Ilham, Zul (Society of Automotive Engineers Malaysia, 2017)
Leucaena leucocephala (petai belalang) seed oil has been studied previously as a feedstock for biodiesel but no study describes its fuel properties for use in diesel engine. In this study, hexane was used to extract oil from the seeds of Leucaena leucocephala in a Soxhlet apparatus. Chemical properties of the oil were then analysed which demonstrated a relatively high FFA content of 6.0wt%, requiring the two-step method for biodiesel production through an acid-catalyzed esterification followed by alkali-catalyzed transesterification. Physico-chemical properties of the processed biodiesel such as triglyceride, diglyceride, monoglyceride, free glycerol, methanol content, ester content, carbon residue, acid value, oxidation stability, tocopherol concentration, iodine value, water content, kinematic viscosity, density, pour point, cloud point, cold filter plugging point and flash point were analysed. The obtained biodiesel showed high oxidation stability and most fuel properties complied with two international standards, European Standards (EN14214) and American Society for Testing Materials (ASTM D6751).